ACRIDOIDEOS (INSECTA: ORTHOPTERA) DEL ESTADO DE GUANAJUATO, MÉXICO - Salas Araiza, Manuel Darío; Salazar Solis, Eduardo; Montesinos Silva, Genaro (Instituto de Ecología, A.C., 2003)
Thirty eight species were determined in 28 genera of the superfamily Acridoidea in the state of Guanajuato. Gomphocerinae belonging to Acrididae, showed the greatest number of genera and species with 11 and 14 respectively; next came Oedipodinae, with six genera and eigth species, and finally Melanoplinae with three genera and four species. Melanoplus differentilis was the most abundant species, constituting about 16% of the total of collected insects; Syrbula admirabilis followed with 12%, and Amblytropidia mysteca and Melanoplus lakinus with nine came in third place. Eleven new records of Acridoidea are reported in the state of Guanajuato. 53% of the genera and 27% of the species reported for Mexico are found in the state of Guanajuato. Melanoplus differentialis and Schistocerca damnifica are the species present in most of the state localities. Some species were only recorded in one locality: Romalea guttata in Atarjea, Chromacris spp. in León, Dicromorpha viridis in Acámbaro, and Dactylotum sp. in Dr. Mora.